Primaquine or other 8-aminoquinoline for reducing Plasmodium falciparum transmission - Graves, Patricia M (Cochrane Database Syst Rev, 2015)
BACKGROUND: Mosquitoes become infected with Plasmodium when they ingest gametocyte-stage parasites from an infected person's blood. Plasmodium falciparum gametocytes are sensitive to the drug primaquine (PQ) and other 8-aminoquinolines (8AQ); these drugs could prevent parasite transmission from infected people to mosquitoes, and consequently reduce the incidence of malaria. However, PQ will not directly benefit the individual, and could be harmful to those with glucose-6-phosphate dehydrogenase (G6PD) deficiency. In 2010, The World Health Organization (WHO) recommended a single dose of PQ at 0.75 mg/kg, alongside treatment for P. falciparum malaria to reduce transmission in areas approaching malaria elimination. In 2013 the WHO revised this to 0.25 mg/kg due to concerns about safety. OBJECTIVES: To assess whether giving PQ or an alternative 8AQ alongside treatment for P. falciparum malaria reduces malaria transmission, and to estimate the frequency of severe or haematological adverse events when PQ is given for this purpose. SEARCH METHODS: We searched the following databases up to 10 Feb 2014 for trials: the Cochrane Infectious Diseases Group Specialized Register; the Cochrane Central Register of Controlled Trials (CENTRAL), published in The Cochrane Library; MEDLINE; EMBASE; LILACS; metaRegister of Controlled Trials (mRCT); and the WHO trials search portal using 'malaria*', 'falciparum', and 'primaquine' as search terms. In addition, we searched conference proceedings and reference lists of included studies, and contacted researchers and organizations. SELECTION CRITERIA: Randomized controlled trials (RCTs) or quasi-RCTs comparing PQ (or alternative 8AQ) given as a single dose or short course alongside treatment for P. falciparum malaria with malaria treatment given without PQ/8AQ in adults or children. DATA COLLECTION AND ANALYSIS: Two authors independently screened all abstracts, applied inclusion criteria, and extracted data. We sought evidence of an impact on transmission (community incidence), infectiousness (mosquitoes infected from humans) and potential infectiousness (gametocyte measures). We calculated the area under the curve (AUC) for gametocyte density over time for comparisons for which data were available. We sought data on haematological and other adverse effects, as well as secondary outcomes of asexual clearance time and recrudescence. We stratified by whether the malaria treatment regimen included an artemisinin derivative or not; by PQ dose category (low < 0.4 mg/kg; medium ≥ 0.4 to < 0.6 mg/kg; high ≥ 0.6 mg/kg); and by PQ schedules. We used the GRADE approach to assess evidence quality. MAIN RESULTS: We included 17 RCTs and one quasi-RCT. Eight studies tested for G6PD status: six then excluded participants with G6PD deficiency, one included only those with G6PD deficiency, and one included all irrespective of status. The remaining ten trials either did not report on whether they tested (8), or reported that they did not test (2). Nine trials included study arms with artemisinin-based malaria treatment regimens, and eleven included study arms with non-artemisinin-based treatments. Only two trials evaluated PQ given at low doses (0.25 mg/kg in one and 0.1 mg/kg in the other). PQ with artemisinin-based treatments: No trials evaluated effects on malaria transmission directly (incidence, prevalence, or entomological inoculation rate), and none evaluated infectiousness to mosquitoes. For potential infectiousness, the proportion of people with detectable gametocytaemia on day eight was reduced by around two thirds with high dose PQ category (RR 0.29, 95% CI 0.22 to 0.37, seven trials, 1380 participants, high quality evidence), and with medium dose PQ category (RR 0.34, 95% CI 0.19 to 0.59, two trials, 269 participants, high quality evidence), but the trial evaluating low dose PQ category (0.1 mg/kg) did not demonstrate an effect (RR 0.67, 95% CI 0.44 to 1.02, one trial, 223 participants, low quality evidence). Reductions in log(10)AUC estimates for gametocytaemia on days 1 to 43 with medium and high doses ranged from 24.3% to 87.5%. For haemolysis, one trial reported percent change in mean haemoglobin against baseline, and did not detect a difference between the two arms (very low quality evidence). PQ with non-artemisinin treatments: No trials assessed effects on malaria transmission directly. Two small trials from the same laboratory evaluated infectiousness to mosquitoes, and report that infectivity was eliminated on day 8 in 15/15 patients receiving high dose PQ compared to 1/15 in the control group (low quality evidence). For potential infectiousness, the proportion of people with detectable gametocytaemia on day 8 was reduced by around half with high dose PQ category (RR 0.44, 95% CI 0.27 to 0.70, three trials, 206 participants, high quality evidence), and by around a third with medium dose category (RR 0.62, 0.50 to 0.76, two trials, 283 participants, high quality evidence), but the single trial using low dose PQ category did not demonstrate a difference between groups (one trial, 59 participants, very low quality evidence). Reduction in log(10)AUC for gametocytaemia days 1 to 43 were 24.3% and 27.1% for two arms in one trial giving medium dose PQ. No trials systematically sought evidence of haemolysis. Two trials evaluated the 8AQ bulaquine, and suggest the effects may be greater than PQ, but the small number of participants (n = 112) preclude a definite conclusion. AUTHORS' CONCLUSIONS: In individual patients, PQ added to malaria treatments reduces gametocyte prevalence when given in doses greater than 0.4 mg/kg. Whether this translates into preventing people transmitting malaria to mosquitoes has rarely been tested in controlled trials, but there appeared to be a strong reduction in infectiousness in the two small studies that evaluated this. No included trials evaluated whether this policy has an impact on community malaria transmission either in low-endemic settings approaching elimination, or in highly-endemic settings where many people are infected but have no symptoms and are unlikely to be treated. For the currently recommended low dose regimen, there is little direct evidence to be confident that the effect of reduction in gametocyte prevalence is preserved. Most trials excluded people with G6PD deficiency, and thus there is little reliable evidence from controlled trials of the safety of PQ in single dose or short course. PLAIN LANGUAGE SUMMARY: A SINGLE DOSE OF PRIMAQUINE ADDED TO MALARIA TREATMENT TO PREVENT MALARIA TRANSMISSION: We conducted a review of the effects of adding a single dose (or short course) of primaquine to malaria treatment with the aim of reducing the transmission of malaria. We included 17 randomized controlled trials and one quasi-randomized controlled trial. What is primaquine and how might it reduce transmission Primaquine is an antimalarial drug which does not cure malaria illness, but is known to kill the gametocyte stage of the malaria parasite which infects mosquitoes when they bite humans. Primaquine is also known to have potentially serious side effects in people with an enzyme deficiency common in many malaria endemic settings (glucose-6-phosphate dehydrogenase (G6PD) deficiency). In these people, high doses of primaquine given over several days sometimes destroys red blood cells, causing anaemia and, in some cases, possibly life-threatening effects. The World Health Organization (WHO) recommends adding a single dose of primaquine to malaria treatment with the intention of reducing malaria transmission and to contribute to malaria elimination. This recommendation was made in 2010, but in 2013 the WHO amended its recommendation from a dose of 0.75 mg/kg to 0.25 mg/kg due to concerns about safety, and indirect evidence suggesting this was as effective as the higher dose.This review examines the evidence of benefits and harms of using primaquine in this way, and looks for evidence that primaquine will reduce malaria transmission in communities. What the research says We did not find any studies that tested whether primaquine added to malaria treatment reduces the community transmission of malaria. When added to current treatments for malaria (artemisinin-based combination therapy), we found no studies evaluating the effects of primaquine on the number of mosquitoes infected. However, primaquine does reduce the duration of infectiousness (the period that gametocytes are detected circulating in the blood) when given at doses of 0.4 mg/kg or above (high quality evidence). We only found one study using 0.1 mg/kg but this study did not conclusively show that primaquine was still effective at this dose (low quality evidence). When added to older treatments for malaria, two studies showed that primaquine at doses of 0.75 mg/kg reduced the number of mosquitoes infected after biting humans (low quality evidence). Doses above 0.4 mg/kg reduced the duration of detectable gametocytes (high quality evidence), but in a single study of the currently recommended 0.25 mg/kg no effect was demonstrated (very low quality evidence). Some studies excluded patients with G6PD deficiency, some included them, and some did not comment. Overall the safety of PQ given as a single dose was poorly evaluated across all studies, so these data do not demonstrate whether the drug is safe or potentially harmful at this dosing level.